Analysis of Site-specific Glycosylation of Renal and Hepatic γ-Glutamyl Transpeptidase from Normal Human Tissue[S] - West, Matthew B.; Segu, Zaneer M.; Feasley, Christa L.; Kang, Pilsoo; Klouckova, Iveta; Li, Chenglong; Novotny, Milos V.; West, Christopher M.; Mechref, Yehia; Hanigan, Marie H. (The Journal of biological chemistry, 2010)
The cell surface glycoprotein γ-glutamyl transpeptidase (GGT) was isolated from healthy human kidney and liver to characterize its glycosylation in normal human tissue in vivo. GGT is expressed by a single cell type in the kidney. The spectrum of N-glycans released from kidney GGT constituted a subset of the N-glycans identified from renal membrane glycoproteins. Recent advances in mass spectrometry enabled us to identify the microheterogeneity and relative abundance of glycans on specific glycopeptides and revealed a broader spectrum of glycans than was observed among glycans enzymatically released from isolated GGT. A total of 36 glycan compositions, with 40 unique structures, were identified by site-specific glycan analysis. Up to 15 different glycans were observed at a single site, with site-specific variation in glycan composition. N-Glycans released from liver membrane glycoproteins included many glycans also identified in the kidney. However, analysis of hepatic GGT glycopeptides revealed 11 glycan compositions, with 12 unique structures, none of which were observed on kidney GGT. No variation in glycosylation was observed among multiple kidney and liver donors. Two glycosylation sites on renal GGT were modified exclusively by neutral glycans. In silico modeling of GGT predicts that these two glycans are located in clefts on the surface of the protein facing the cell membrane, and their synthesis may be subject to steric constraints. This is the first analysis at the level of individual glycopeptides of a human glycoprotein produced by two different tissues in vivo and provides novel insights into tissue-specific and site-specific glycosylation in normal human tissues.